Specific Aptamer-Based Probe for Analyzing Biomarker MCP Entry Into Singapore Grouper Iridovirus-Infected Host Cells via Clathrin-Mediated Endocytosis - Yu, Qing; Liu, Mingzhu; Wu, Siting; Wei, Xinxian; Xiao, Hehe; Yi, Yi; Cheng, Hao; Wang, Shaowen; Zhang, Qin; Qin, Qiwei; Li, Pengfei (Frontiers in Microbiology, 2020)
Biomarkers have important roles in various physiological functions and disease pathogenesis. As a nucleocytoplasmic DNA virus, Singapore grouper iridovirus (SGIV) causes high economic losses in the mariculture industry. Aptamer-Q5-complexed major capsid protein (MCP) in the membrane of SGIV-infected cells can be used as a specific molecular probe to investigate the crucial events of MCP endocytosis into SGIV-infected host cells during viral infection. Chlorpromazine blocks clathrin-mediated endocytosis, and MCP endocytosis into SGIV-infected cells decreased significantly when the cells were pretreated with chlorpromazine. The disruption of cellular cholesterol by methyl-β-cyclodextrin also significantly reduced MCP endocytosis. In contrast, inhibitors of key regulators of caveolae/raft-dependent endocytosis and macropinocytosis, including genistein, Na+/H+ exchanger, p21-activated kinase 1 (PAK1), myosin II, Rac1 GTPase, and protein kinase C (PKC), had no effect on MCP endocytosis. The endocytosis of the biomarker MCP is dependent on low pH and cytoskeletal actin filaments, as shown with various inhibitors (chloroquine, ammonia chloride, cytochalasin D). Therefore, MCP enters SGIV-infected host cells via clathrin-mediated endocytosis, which is dependent on dynamin, cholesterol, low pH, and cytoskeletal actin filaments. This is the first report of a specific aptamer-based probe used to analyze MCP endocytosis into SGIV-infected host cells during viral infection. This method provides a convenient strategy for exploring viral pathogenesis, and facilitates the development of diagnostic tools for and therapeutic approaches to viral infection.